The Economics of Small Businesses An International Perspective - Calcagnini, Giorgio; Favaretto, Ilario; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2011)
Is small still beautiful? The recent economic and financial crisis has shown that developed countries in which firms are smaller suffered the biggest GDP plunges. Today, economic growth depends more than in the past on sound and well-organized firms, which means more innovation, a better educated labor force, higher likelihood of access to financial resources and efficient investments. This does not mean the end of small-sized firms, but that they need to be different from the way they were in the past. This book provides an international perspective on analyses and policy recommendations for how small businesses can reinforce their role in modern economies.
Keywords: Economics; Economic policy; Regional economics; Economics/Management Science; Economic Policy; Regional/Spatial Science